2017
DOI: 10.3390/molecules22030401
|View full text |Cite
|
Sign up to set email alerts
|

Camellia sinensis L. Extract and Its Potential Beneficial Effects in Antioxidant, Anti-Inflammatory, Anti-Hepatotoxic, and Anti-Tyrosinase Activities

Abstract: The aims of this study were to investigate the potential benefits of antioxidant, anti-inflammatory, anti-hepatotoxic, and anti-tyrosinase activities of a methanolic extract of fresh tea leaves (FTE) (Camellia sinensis L.). The antioxidant capacity was investigated using three different methods at different temperatures. The anti-inflammatory activity was studied in vitro by the inhibition of 5-lipoxygenase assay. The anti-hepatotoxic effect was investigated in CCl4-induced liver injury in rats. The anti-tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
1
18
0
2
Order By: Relevance
“…차잎에는 카테킨과 플라보노 이드계 등의 폴리페놀 화합물이 건조중량 대비 10-25% 들어있 으며 [1], 차잎의 폴리페놀의 75% 이상을 차지하는 카테킨류의 주요 화합물로는 (+)-catechin, (−)-epicatechin, (−)-epigallocatechin, (−)-epigallocatechin gallate, (−)-epicatechin gallate 등 이 알려져 있다 [2]. 차잎의 폴리페놀은 강력한 천연 항산화 물 질로서 항염증, 항돌연변이 및 항암 효과를 가지고 있고 [3,4], 고혈압과 동맥경화 억제 등의 심혈관계 질환을 예방하는 물질 로 알려져 있다 [5,6].…”
Section: 서 론unclassified
“…차잎에는 카테킨과 플라보노 이드계 등의 폴리페놀 화합물이 건조중량 대비 10-25% 들어있 으며 [1], 차잎의 폴리페놀의 75% 이상을 차지하는 카테킨류의 주요 화합물로는 (+)-catechin, (−)-epicatechin, (−)-epigallocatechin, (−)-epigallocatechin gallate, (−)-epicatechin gallate 등 이 알려져 있다 [2]. 차잎의 폴리페놀은 강력한 천연 항산화 물 질로서 항염증, 항돌연변이 및 항암 효과를 가지고 있고 [3,4], 고혈압과 동맥경화 억제 등의 심혈관계 질환을 예방하는 물질 로 알려져 있다 [5,6].…”
Section: 서 론unclassified
“…In line with this, some studies have shown the effects of curcumin supplementation on OS, inflammation, EIMD, and sport performance with controversial results. These inconsistent results may be due, in part, to differences in doses, timing of supplementation, timing of exercise, exercise model, and experimental design between studies [23]. Previous research has indicated that curcumin may have antioxidant, anti-inflammatory, and analgesic effects on DOMS [24].…”
Section: Introductionmentioning
confidence: 99%
“…4 Nutricosmetics containing antioxidants and anti-aging properties may be useful and are simple to use as a part of treatment. 14,15 Depigmenting peelings used in association with trichloroacetic acid, ascorbic and phytic acids represent an effective option. 9,10 One study concluded that the combination of 20% TCA with 5% ascorbic acid was a highly effective and well-tolerated therapy with low recurrence of melasma.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 More recently, systemic approaches for the treatment of melasma have been proposed. There is a growing interest in oral antioxidant supplements like extract of Polypodium leucotomos, green tea extract and vitamin C. [13][14][15] These ingredients improve photoprotection by decreasing the production or limiting the effect of the oxidative stress. Their effect in melasma is, however, poorly documented.…”
Section: Introductionmentioning
confidence: 99%